Diversity of Gastrointestinal Parasites in Endangered Sumatran Elephants (Elephas maximus sumatranus Temminck, 1847) at Taman Margasatwa Ragunan, Jakarta Selatan - Ilmia Rosame; Luthfiralda Sjahfirdi; Siti Nursheena Mohd Zain (Postgraduate, University of Mataram, 2025)
Parasitic infections in elephants in captivity is not well studied. Animals in captivity are susceptible to parasitic infections because they are prone to stress, which reduces their immune response. Therefore, this study aimed to identify gastrointestinal parasite infections among captive sumatran elephants in Taman Margasatwa Ragunan (TMR). A total of 86 fecal samples were obtained from 4 individual Sumatran elephants, conducted in October-December 2024. Screening of GIPs was carried out using the concentration sedimentation method. A total of 3 GIPs were recovered with the prevalence of hookworm and Balantidium coli is the highest (100%) and Strongyloides sp. (25%). Although there are some parasites found in faeces, Sumatran elephants in TMR There are no specific symptoms associated with the parasite. There is no parasite prevention and control management, such as routine monitoring or administration of anti-parasitic drugs to elephants at TMR. Management and control of parasitic infections needs to be improved to prevent the infection from getting worse and suppress parasite transmission.